Deteksi Dini Gangguan Pertumbuhan dan Perkembangan Anak - Atien Nur Chamidah (Universitas Negeri Yogyakarta, 2009)
Growth and development process can show the quality of child. Growth and development process which started from prenatal phase is a result of interaction between genetic factor and environment factor. The process has faster improvement on early age, 0-5 years old which is called